Accounting Conservatism, Firm Size, Company Growth, and Capital Structure on Earnings Response Coefficient in Property Companies: Konservatisme Akuntansi, Ukuran Perusahaan, Pertumbuhan Perusahaan, dan Struktur Modal terhadap Koefisien Respon Laba pada Perusahaan Properti - Pangestu, Melania; Hariyanto, Wiwit (Indonesian Journal of Innovation Studies, 2023)
This research aimed to examine the effect of accounting conservatism, firm size, company growth, and capital structure on the earnings response coefficient. This research method uses quantitative research methods, data collection used documentation studies in the form of secondary data sources of financial statements and stock prices in Property, Real Estate, and Building Construction companies listed on the IDX in 2017-2019. The research’s population are the Property, Real Estate, and building construction companies listed on Indonesian Stock Exchange period 2017-2019 as much as 81 companies. Sampling method were selected by using non probability sampling purposive sampling with certain criteria and obtained as much as 34 companies. Anlyze the data used SPSS 26. The result shows that accounting conservatism, firm size, and company growth have no effect on the earnings response coefficient while capital structure has effect and significant on the ernings response coefficient.